Modelling the rate and temperature-dependent behaviour and texture evolution of the Mg AZ31B alloy TRC sheets. Issue 4 (1st February 2018) - Ayoub, G.; Rodrigez, A. K.; Shehadeh, M.; Kridli, G.; Young, J. P.; Zbib, H.
Abstract: In this work, the mechanical behaviour and texture evolution of AZ31B magnesium alloy under uniaxial tensile testing are investigated at different strain rates and temperatures. A crystal plasticity model is developed and calibrated to predict the mechanical response of the AZ31B at different temperatures and strain rates. The model results show that the relative activity of the pyramidal slip increases with increasing temperature, reaching a maximum activity at 200 °C. In order to achieve the continuous increase in the relative activity of the pyramidal slip as reported in the literature, a grain boundary sliding mechanism is implemented in the crystal plasticity framework. The incorporation of the grain boundary sliding at elevated temperatures results in considerable improvement in the model's capabilities for prediction of yielding, hardening and texture evolution.